2014
DOI: 10.2967/jnumed.113.130161
|View full text |Cite
|
Sign up to set email alerts
|

Activity of P-Glycoprotein, a β-Amyloid Transporter at the Blood–Brain Barrier, Is Compromised in Patients with Mild Alzheimer Disease

Abstract: Animal and histopathological studies of human brain support a role for P-glycoprotein (P-gp) in clearance of cerebral β-amyloid (Aβ) across the blood brain barrier (BBB). We tested the hypothesis that BBB P-gp activity is diminished in Alzheimer’s disease (AD) by accounting for AD-related reduction in regional cerebral blood flow (rCBF). Methods We compared P-gp activity in mild AD patients (n=9) and cognitively normal, age-matched controls (n=9) using positron emission tomography (PET) with a labeled P-gp su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(154 citation statements)
references
References 37 publications
11
135
2
1
Order By: Relevance
“…Similarly, as previously demonstrated by us and others (Sasongko et al, 2005;Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Bauer et al, 2012;Mullauer et al, 2012;Bankstahl et al, 2013;Ke et al, 2013;Deo et al, 2014), when a drug is effluxed out of the brain, its concentration in the brain can be much lower than that in the plasma. This disconnect between tissue and plasma drug concentration will be modulated in the presence of a drug-drug interaction (DDI).…”
Section: Quantification Of Drug Transporters To Understand Interindivsupporting
confidence: 76%
See 1 more Smart Citation
“…Similarly, as previously demonstrated by us and others (Sasongko et al, 2005;Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Bauer et al, 2012;Mullauer et al, 2012;Bankstahl et al, 2013;Ke et al, 2013;Deo et al, 2014), when a drug is effluxed out of the brain, its concentration in the brain can be much lower than that in the plasma. This disconnect between tissue and plasma drug concentration will be modulated in the presence of a drug-drug interaction (DDI).…”
Section: Quantification Of Drug Transporters To Understand Interindivsupporting
confidence: 76%
“…Such data are best obtained using noninvasive imaging methods (such as PET imaging) to determine drug transport concentrations in various tissues (e.g., brain, fetus, and liver). Such data are available from our laboratory (Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Ke et al, 2013;Deo et al, 2014;He et al, 2014) and others. Therefore, the accuracy of the above proposed IVIVE method can now be tested.…”
Section: Quantification Of Drug Transporters To Understand Interindivmentioning
confidence: 99%
“…Furthermore, the same authors also observed a negative correlation between capillary Pgp expression and neurofibrillary tangles in AD brains. Importantly, the activity of this BBB transporter was also reduced in several brain regions, including the hippocampus, of mild AD patients [122]. The mechanism underlying Pgp action in limiting Aβ accumulation in the brain is still under debate, with studies pointing to the clearance of Aβ from the abluminal to the luminal side of the membrane, while others indicate that the strategic position of the transporter at the luminal side of the BBB limits Aβ entry into the brain [123].…”
Section: Changes In Amyloid-β Transportersmentioning
confidence: 98%
“…The advantage of the statistical mapping is that no assumption is made regarding the relevant regions and that it can be used to analyze the entire tissue observed in the image (e.g., brain) (28). Thus, it can detect changes outside a priori specified regions and is therefore useful for identification of regional changes in transporter activity, e.g., in epilepsy (39) and Alzheimer's disease (40,41), and potentially also in tumors and their metastases.…”
Section: Quantification Of Imaging Datamentioning
confidence: 99%